2023
DOI: 10.1126/scitranslmed.adf3843
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular trap production and CCL4L2 expression influence corticosteroid response in asthma

Abstract: The association between neutrophil extracellular traps (NETs) and response to inhaled corticosteroids (ICS) in asthma is unclear. To better understand this relationship, we analyzed the blood transcriptomes from children with controlled and uncontrolled asthma in the Taiwanese Consortium of Childhood Asthma Study using weighted gene coexpression network analysis and pathway enrichment methods. We identified 298 uncontrolled asthma-specific differentially expressed genes and one gene module associated with neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Our study has limitations: while we establish correlations between NETs components, disease severity, and NF-kB-dependent cytokines levels in BALF of patients with COPD adhering to standard LAMA or ICS + LABA therapies, we lack information on individual pharmacological regimens that might impact MPO and NE levels. This is particularly pertinent given previous studies suggesting an association between NETs abundance and ICS resistance or ICS regular use in patients with asthma, 62 , 63 implying potential interactions between NETosis and ICS therapy. Future research could benefit from incorporating detailed clinical records to elucidate how current therapeutic strategies influence CS-induced NETosis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our study has limitations: while we establish correlations between NETs components, disease severity, and NF-kB-dependent cytokines levels in BALF of patients with COPD adhering to standard LAMA or ICS + LABA therapies, we lack information on individual pharmacological regimens that might impact MPO and NE levels. This is particularly pertinent given previous studies suggesting an association between NETs abundance and ICS resistance or ICS regular use in patients with asthma, 62 , 63 implying potential interactions between NETosis and ICS therapy. Future research could benefit from incorporating detailed clinical records to elucidate how current therapeutic strategies influence CS-induced NETosis.…”
Section: Discussionmentioning
confidence: 93%
“…mice (scale bar: 100 μm, Supplementary Method 24), as summarised in (p) normalised area of NETs impact MPO and NE levels. This is particularly pertinent given previous studies suggesting an association between NETs abundance and ICS resistance or ICS regular use in patients with asthma, 62,63 implying potential interactions between NETosis and ICS therapy. Future research could benefit from incorporating detailed clinical records to elucidate how current therapeutic strategies influence CS-induced NETosis.…”
Section: Discussionmentioning
confidence: 95%
“…To investigate this in more detail, we collected the bronchoalveolar lavage fluid (BALF) of the experimental mice and subjected it to an ELISA. [ 56 ] The results revealed that TLPG A but not LPG A treatment significantly reduced the production of OVA‐induced pro‐inflammatory cytokines in the lungs of model mice (Figure S23 , Supporting Information). In addition, the inflammatory score, calculated from the images of H&E‐stained lung sections, decreased from 3.3±0.8 to 2.0±0.9 after TLPG A treatment (Figure S24 , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the inflammatory score, calculated from the images of H&E‐stained lung sections, decreased from 3.3±0.8 to 2.0±0.9 after TLPG A treatment (Figure S24 , Supporting Information). [ 56 ] Excessive EET formation was also observed in the lungs of mice with eosinophilic airway inflammation versus those of sham mice (22.3±4.0% and 6.2±1.3%); moreover, TLPG A treatment reduced the EET area in the lungs more effectively than LPG A administration (11.6±2.9% and 15.2±1.4%, respectively) (Figure S25 , Supporting Information). Although TLPG A reduced inflammation in the lungs of model mice, its effect was much lower than that observed in the nasal cavity; this difference may be due to the relatively low accumulation of nanomaterials in the lungs after i.n.…”
Section: Resultsmentioning
confidence: 99%
“…Significantly, NETs are intricately interwoven into the inflammatory immune cascade, actively contributing to the generation of IL-6 and IL-8 by epithelial cells. , Furthermore, they directly stimulate immune cells, notably macrophages and dendritic cells (DCs), amplifying the immune response. , Pertinently, the presence of activated neutrophils in the mucosa of individuals with airway inflammation underscores the activation of neutrophils upon ingress into the inflammatory microenvironment . Excessive NET formation has been implicated as a catalyst for persistent inflammation, and notably, standard therapeutics such as glucocorticoids (GCs) exhibit limited effectiveness in suppressing NET generation, possibly contributing to therapy resistance …”
Section: Introductionmentioning
confidence: 99%